2019
DOI: 10.1039/c8en01119b
|View full text |Cite
|
Sign up to set email alerts
|

The first comprehensive safety study of Magnéli phase titanium suboxides reveals no acute environmental hazard

Abstract: This study provides the first evidence that the tested Magnéli TiOx are not acutely hazardous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The Magnely phases have remarkable properties as high electrical conductivity, high corrosion resistance, and optical properties, among others (Harada, Tanaka, & Inui, 2010; Ioroi et al, 2008; Lu et al, 2011). Recently, Jemec Kokalj et al (2019) evaluated the environmental hazard of titanium suboxides on six organisms and two human cell lines. They found that Magnely phases can be classified as nonhazardous material.…”
Section: Discussionmentioning
confidence: 99%
“…The Magnely phases have remarkable properties as high electrical conductivity, high corrosion resistance, and optical properties, among others (Harada, Tanaka, & Inui, 2010; Ioroi et al, 2008; Lu et al, 2011). Recently, Jemec Kokalj et al (2019) evaluated the environmental hazard of titanium suboxides on six organisms and two human cell lines. They found that Magnely phases can be classified as nonhazardous material.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at , File S1: metadata for Figures S1–S4 (main text); Figure S5: 3-parameter log-logistic concentration–response model fittings of RGR frond ; Figure S6: 3-parameter log-logistic concentration–response model fittings of F v /F o ; Figure S7: 3-parameter log-logistic concentration–response model fittings of Y(II); and Table S1: The results of the 3-parameter log-logistic model fittings with calculated EC 20 and EC 50 values for the studied endpoints. References [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ,…”
mentioning
confidence: 99%
“…[14][15][16] While issues of lead and antimony toxicity have limited the use of PbO 2 and ATO, the latter also exhibiting poor stability, 17 MPTOs are emerging as a viable alternative to BDD. MPTOs are nontoxic, 18 excellent electrical conductors whose single-crystal conductivity exceeds 1,000 S cm 1 , 19 dimensionally stable in aggressive media such as nitric and hydrofluoric acid, 20 and inexpensive at <0.5 USD m 2 . 12 Preliminary studies of the EO of wastewater impacted by synthetic organic dyes with MPTO electrodes demonstrate their effectiveness for decolorization and chemical oxygen demand (COD) removal.…”
mentioning
confidence: 99%